2006
DOI: 10.1007/s00464-004-2186-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hepatic resection

Abstract: Hepatic resection with laparoscopy is feasible in malignant and benign hepatic lesions located in the left lobe and anterior inferior right lobe segments (IV, V, and VI). Results are similar to those of the open surgical technique in carefully selected cases, although studies with large numbers of patients are necessary to drawn definite conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Although the percentage of liver resections performed by laparoscopy remained low in the current study, it has greatly increased since the beginning of our experience in 1999. Indeed, for the last 2 years, 80% of left lateral lobecto- (24) APVC, anatomic with prior vascular control [2,4,29], the rate of resected benign lesions still is high. This is not because of a change in the therapeutic policy for benign liver tumors, but because most benign lesions were resected by laparoscopy due to the fact that they generally arise in normal livers [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although the percentage of liver resections performed by laparoscopy remained low in the current study, it has greatly increased since the beginning of our experience in 1999. Indeed, for the last 2 years, 80% of left lateral lobecto- (24) APVC, anatomic with prior vascular control [2,4,29], the rate of resected benign lesions still is high. This is not because of a change in the therapeutic policy for benign liver tumors, but because most benign lesions were resected by laparoscopy due to the fact that they generally arise in normal livers [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recently a number of case series have been published detailing the feasibility and safety of the laparoscopic approach for liver resection [11,12,13]. LLLS has been considered the most suitable anatomical resection for the laparoscopic approach and as an entry procedure to laparoscopic liver surgery [4].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the rate of benign lesions for LLR was high [1, 2] because the lesions were in the normal liver, not in chronic damaged liver [4]. Based on our cases, the resection rate of malignant lesions was 76.5%, including 15 cases of HCC with liver cirrhosis.…”
Section: Discussionmentioning
confidence: 56%
“…A number of authors have recently been reported the results of their cumulative experience using laparoscopic liver resection [1][2][3][4][5][6][7][8]. In this paper, we report our experience with this technique from the point of view of safety and effectiveness.…”
Section: Introductionmentioning
confidence: 99%